Cognition toward the mother tongue, attitude toward English, Chavacano, and Filipino: A structural equation modeling approach with bootstrap analysis - Go Silk, Byron B. (Animo Repository, 2020)
This quantitative investigation involved 1,054 pre-service teacher respondents with mean age = 20.21 (SD=3.124). This cross-sectional study gathered data through the creation of four research tools validated and pilot tested. Moreover, three of the research tools (AChavQ, AFilQ, AEngQ) were determined to be of ‘excellent’ reliability, while one is of ‘acceptable’ reliability (CogMT). The study purposed to derive a model explaining the possible relationships, mediation or moderation, of language attitude towards Chavacano with ethnicity, cognition towards mother tongue and language attitude toward Filipino and English. The model with “best fit” showed that that language attitude toward Filipino and English has a direct influence on cognition in the mother tongue. In contrast, ethnicity’s influence is mediated by language attitude toward Chavacano. The results and findings of this study provide vital information and insights in the implementation of the Mother Tongue Based Education in a multilingual context. © 2020 Asian EFL Journal Press. All rights reserved.